A Bis‐heteroleptic Imidazolium‐bipyridine Functionalized Iridium(III) Complex for Fluorescence Lifetime‐based Recognition and Sensing of Phosphates. Issue 15 (15th June 2022) - Rashid, Ambreen; Mondal, Sahidul; Mondal, Subal; Ghosh, Pradyut
Abstract: A new Ir III based 3, 3′‐([2, 2′‐bipyridine]‐5, 5′‐diylbis(methylene))bis(1‐ethyl‐1H‐imidazol‐3‐ium) functionalized receptor Ir‐1 has been synthesized for selective recognition, sensing and as a lifetime based sensor for H2 PO4 − and HP2 O7 3− in acetonitrile. An increase in the lifetime (τ) from 0.03543 μs to 0.2736 μs and 0.1323 μs in the presence of H2 PO4 − and HP2 O7 3−, respectively, among all other competitive anions establishes Ir‐1 as a simple lifetime‐based sensor. Furthermore, 13.7‐ and 8.5‐fold enhancement in PL intensities of Ir‐1 along with blue‐shifting is seen with H2 PO4 − and HP2 O7 3−, respectively. High selectivity of Ir‐1 for these two ions even in the presence of a large excess of other anions also displayed sensitive detection (LOD=0.035 μM for HP2 O7 3− and 0.040 μM for H2 PO4 − ). NMR data further suggest that the recognition of phosphates by Ir‐1 is occurring through C−H⋅⋅⋅phosphate hydrogen bond (HB) interaction. Abstract : An iridium polypyridine complex Ir‐1 has been prepared and assessed for recognition and sensing of phosphate anions. A selective, sensitive and lifetime‐based detection of phosphates in the presence of other anions was displayed. An increase in the lifetimes accompanied with enhancement in PL intensities of Ir‐1 is seen with H2 PO4 − and HP2 O7 3− .